2007
DOI: 10.1115/1.2768088
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Cavitation Model in the Analysis of Microtextured Lubricated Journal Bearings

Abstract: In this paper, we analyze the impact of the cavitation model on the numerical assessment of lubricated journal bearings. We compare results using the classical Reynolds model and the so-called p-θ model proposed by Elrod and Adams [1974, “A Computer Program for Cavitation and Saturation Problems,” Proceedings of the First LEEDS-LYON Symposium on Cavitation and Related Phenomena in Lubrication, Leeds, UK] to fix the lack of mass conservation of Reynolds’ model. Both models are known to give quite similar predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(197 citation statements)
references
References 12 publications
9
176
0
Order By: Relevance
“…Half Sommerfeld condition [21], Reynolds cavitation boundary condition [15,16] and JFO (JakobssonFloberg-Olsson) condition [15,17] in a p-θ model are usually utilized in the analysis when using the Reynolds equation. And several cavitation models [19,22,23] in CFD analysis are also used.…”
Section: Resultsmentioning
confidence: 99%
“…Half Sommerfeld condition [21], Reynolds cavitation boundary condition [15,16] and JFO (JakobssonFloberg-Olsson) condition [15,17] in a p-θ model are usually utilized in the analysis when using the Reynolds equation. And several cavitation models [19,22,23] in CFD analysis are also used.…”
Section: Resultsmentioning
confidence: 99%
“…These algorithms are the present algorithm (JFO-FEM), finite difference method with JFO cavitation theory (JFO-FDM) from (Ausas et al, 2007;2009) and FEM with Reynolds cavitation boundary condition (REYNOLDS-FEM). According to REYNOLDS-FEM, Uzawa's algorithm (Ito and Kunisch, 2003) was applied to assure pressure satisfying the Reynolds boundary condition.…”
Section: Validationsmentioning
confidence: 99%
“…Because the above -g model gives an unrealistic fluid film fraction (larger than 1) in the full film region for the numerical reasons from the choice of proper bulk modulus, a p-model is frequently used in various studies, where the JFO cavitation boundary is converted into a complementarity condition. According to the model, Ausas et al (2007;2009) presented an effective relaxation scheme to update the solution of satisfying complementarity conditions. Due to the capability of FEM to create a complex boundary, it was first introduced into the prediction of cavitation regions with the JFO theory by Kumar and Booker (1991; and Boedo and Booker (1995), who used Murty (1988)'s algorithm to distinguish the film rupture and reformation boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the load-carrying capacity arising from the micro wedge action seems doubtful because the significant low load-carrying capacity has been determined [25,26], taking into account the mass conservation of flow between the cavitation zone and the pressure-developed zone. Therefore, the present study focuses on quantifying the extent of the load-carrying capacity enabled by the micro wedge action.…”
Section: Introductionmentioning
confidence: 99%
“…Following the development of the Elrod algorithm, several researchers revised the algorithm and used it in their studies [23,24]. Ausas et al [25] and Qiu and Khonsari [26] used the Elrod algorithm to compare the load-carrying capacity determined using the Reynolds boundary condition to that determined using the JFO theory. It was found that the load-carrying capacity is overestimated when the Reynolds boundary condition is used to consider the cavitation zone.…”
Section: Introductionmentioning
confidence: 99%